Secure Key Management for Flexible Digital Rights Management of Scalable Codestreams - Zhu, Bin Benjamin; Feng, Min; Li, Shipeng (IEEE Int. Workshop Multimedia Signal Processing (MMSP) 2005, 2005)
The key management for multi-type, multi-level scalable access control of a fine granularity scalability codestream is addressed in this paper. We first present an efficient partially ordered set (poset) to represent scalable access control so that any access control schemes for a poset can be applied and a single secret key is needed to transfer to a user. We then present a secure key scheme modified from our previous scalable access key scheme for the resulting poset. The key scheme is based on the group Diffie-Hellman key agreement, and is secure.